Creation of a CASPER Survey Protocol for Use in Riley County, Kansas - DeFisher, Jason (My University, 2021)
The Centers for Disease Control (CDC) developed the Community Assessment for Public Health Emergency Response (CASPER) survey toolkit as a standardized two-stage cluster sample method for rapid needs assessments. The CASPER survey was originally intended to assist in the collection of public health data in times of emergency, such as natural disasters, but it has also been used to collect health data in non-emergency situations. This includes the collection of data to inform Community Health Improvements Plans (CHIP). The primary objective of this collaborative group project was to adapt the CASPER toolkit for use in Riley County, Kansas. The adapted protocol was to be created by the efforts of a collaboration with the Riley County Health Department (RCHD), but it was intended for use by both RCHD and community partners wishing to collect community health data within the county. The protocol creation began with literature review to gain a better understanding of a full CASPER process. Literature reviewed included the CDC CASPER toolkit as well as published CASPER reports from health departments in Texas and Montana. During literature review, the CDC was also contacted for clarifications and assistance using the official email set up by the CDC for CASPER assistance. After sufficient literature was reviewed, supplementary protocol documents were produced by the Master of Public Health (MPH) students collaborating on the project. These documents were intended to provide templates and guides to assist future CASPER organizers in preparing, conducting, and reporting the completed CASPER process. Following the document preparation, the students planned and organized a test run of the CASPER protocol. The test survey was intended to be at least a 10% scale of a full CASPER in order to provide an efficient practice run with limited time and resources. Four clusters, predetermined areas defined by US Census blocks, within Manhattan were selected to simulate a random selection of clusters from the full list of Riley County’s census blocks. Volunteers for conducting the survey were gathered from Kansas State University (KSU) students involved in the MPH program and personal contacts of the students involved in the survey organization. The templates and guides were then compiled into a comprehensive guide for Riley County and presented to RCHD. The students also presented their protocol and work to the Flint Hills Wellness Coalition to promote its use among community partners.
Keywords: CASPER; Survey; Protocol; Development